2020
DOI: 10.3390/ijerph17072212
|View full text |Cite
|
Sign up to set email alerts
|

What Protects Youth Residential Caregivers from Burning Out? A Longitudinal Analysis of Individual Resilience

Abstract: Background: Professional caregivers are exposed to multiple stressors and have high burnout rates; however, not all individuals are equally susceptible. We investigated the association between resilience and burnout in a Swiss population of professional caregivers working in youth residential care. Methods: Using a prospective longitudinal study design, participants (n = 159; 57.9% women) reported on burnout symptoms and sense of coherence (SOC), self-efficacy and self-care at four annual sampling points. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 61 publications
3
6
0
1
Order By: Relevance
“…In line with previous studies, we found that self-oriented empathy could negatively predict dispositional mindfulness ( Baer, 2004 ; Dekeyser et al, 2008 ; Fuochi and Voci, 2020 ) and context-specific self-efficacy ( Aparicio-Flores et al, 2020 ). We also found that low levels of mindfulness and context-specific self-efficacy were associated with a high level of CF, which is consistent with previous studies ( Olson et al, 2015 ; Shoji et al, 2015 ; Brown et al, 2017 ; Kind et al, 2020 ). Moreover, our results supported the hypotheses that self-oriented empathy would be associated with CF via dispositional mindfulness and counselor’s self-efficacy, respectively, which suggests that self-oriented empathy could affect CF partially through awareness in the present and beliefs on the professional ability.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, we found that self-oriented empathy could negatively predict dispositional mindfulness ( Baer, 2004 ; Dekeyser et al, 2008 ; Fuochi and Voci, 2020 ) and context-specific self-efficacy ( Aparicio-Flores et al, 2020 ). We also found that low levels of mindfulness and context-specific self-efficacy were associated with a high level of CF, which is consistent with previous studies ( Olson et al, 2015 ; Shoji et al, 2015 ; Brown et al, 2017 ; Kind et al, 2020 ). Moreover, our results supported the hypotheses that self-oriented empathy would be associated with CF via dispositional mindfulness and counselor’s self-efficacy, respectively, which suggests that self-oriented empathy could affect CF partially through awareness in the present and beliefs on the professional ability.…”
Section: Discussionsupporting
confidence: 92%
“…These cross-sectional correlational findings might be a first indicator of this possible health promoting effect and should be further investigated in larger longitudinal interventional studies. In a recent longitudinal study, we were able to demonstrate that SoC and self-caring behavior in youth residential caregivers protect against burnout (40). The current findings extend the protective role of resilience onto psychophysiological alterations in hair samples of caregivers.…”
Section: Discussionsupporting
confidence: 72%
“…SoC and self-efficacy are well and broadly studied concept, whereas for self-care to date there is no clear and homogenous construct defined in the literature and it is very heterogeneously assessed. These concepts were found to be moderately correlated with one another ( 40 ), which complicates individual interpretations if combined in the same model, therefore we decided to analyze them separately.…”
Section: Discussionmentioning
confidence: 99%
“…GRR can include characteristics of an individual, a group or an environment (genetic, physical, and psychosocial), which might ease effective tension management (38). Numerous studies have shown SoC to be positively related to health-behaviors and mental health and negatively toward burnout, depression, anxiety and PTSD symptoms in caregivers and medical staff (1,26,(39)(40)(41). Others showed SoC to be an important moderator and mediator between chronic stressors, early adversity and later health outcomes (42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation